Assessment of memory in patients with rheumatoid arthritis - Tomašević-Todorović Snežana; Bošković Ksenija; Filipović Danka; Naumović Nada (Vojnosanitetski Pregled)
Background/Aim. The diagnosis of emotional and cognitive dysfunction in patients with rheumatoid arthritis is often not noticed, regardless of their importance and frequency. The aim of this research was to assess memory function in patients with rheumatoid arthritis with respect to its emotional manifestation, pain intensity, the duration and degree of disease activity, and functional and anatomical stages of the disease. Methods. The study involved 60 patients with rheumatoid arthritis and 30 healthy subjects of both sexes, aged up to 55, who were examined and tested in the Special Hospital for Rheumatic Diseases in Novi Sad. Depression was diagnosed by using the Beck’s scale for depression (Beck Depression Inventory - BDI), anxiety by using the Spielberger Trait Anxiety Inventory - State and Traité; we evaluated the cognitive status (by the Wechsler scale-based memory - WBsp), the functional status (Health Assesment Questionnaire, HAQ) and disease activity by analyzing the index of disease activity (DAS 28). Results. Depressive symptoms were registered in 38 (63.33%) patients, and anxiety symptoms in 22 (36.67%) patients. The average values of the memory coefficient were significantly lower in the group of patients with rheumatoid arthritis compared with the control group. Conclusion. High frequency of emotional dysfunction and damaged memory abilities in patients with rheumatoid arthritis requires in time diagnosis and adequate treatment.